Urgent Hospital Admissions Caused by Adverse Drug Reactions and Medication Errors—A Population-Based Study in Spain - Mejía, Gina; Saiz-Rodríguez, Miriam; Gómez de Olea, Beatriz; Ochoa, Dolores; Abad-Santos, Francisco (Frontiers in Pharmacology, 2020)
Background – Adverse drug reactions (ADRs) are a public health issue, due to their great impact on morbidity, mortality and economic cost. Objective – We aimed to study the percentage of patients admitted urgently as a result of an ADR, considered serious adverse event, or medication error. Also, we intended to identify possible risk factors which would lead to improvements in the prescription and use of medications. Methods – This is a retrospective observational study conducted during February 2019, including patients admitted through the emergency department in our hospital. We evaluated the medical records of those with suspected ADR diagnoses to perform a descriptive analysis of the demographic characteristics. Moreover, after applying the Spanish Pharmacovigilance System causality algorithm, we performed a descriptive analysis of the identified ADRs and the drugs involved. We also investigated those cases suspected of being a medication error. Results – During the study period, 847 patients were urgently hospitalized. From those, 71 (29 women and 42 men) were admitted due to an ADR (8.4%, 95% CI 6.5-10.3%). The mean age was 73  15.9 years old and the mean number of prescribed medications was 7.3  3.6 drugs/patient on admission. The most frequent ADRs were opportunistic infections due to antineoplastic and immunomodulator drugs, and bleeding due to antiaggregants and anticoagulants. Five suspected medication errors occurred, being the incidence 0.6% (95% CI 0.08-1.12%) of total admissions. Conclusions – 8.4% of urgent admissions were attributed to an ADR. Age, comorbidities and polymedication were the main risk factors. Although medication errors had a very low incidence (0.6% of urgent admissions), they were preventable and should be considered as a focus for action.